Redefining the waste: Sustainable management of olive mill waste for the recovery of phenolic compounds and organic acids - Guvem, Sevval Aleyna; Ozbey-Unal, Bahar; Keskinler, Bülent; Balçık, Çiğdem (Elsevier, 2024)
The olive oil industry generates significant amounts of olive mill waste (OMW), which poses environmental challenges due to its high organic load and phenolic content. This study investigates an eco-friendly approach to managing OMW by recovering valuable phenolic compounds (PCs) and volatile fatty acids (VFAs) through an integrated process. The methodology involves a filter press, followed by a self-cleaning mechanical vapor recompression (SCMVR) process for water and volatile compounds separation, and a subsequent liquid-liquid extraction for PCs. 99 % of the VFAs were recovered as organic acid salts from the SCMVR distillate and characterized using X-Ray diffraction (XRD) analysis. The Box-Behnken design (BBD) of response surface methodology (RSM) was used to optimize the extraction process, considering variables such as solvent type, pH, temperature, and extraction time. The liquid-liquid extraction process yielded a 98 % recovery of PCs with twostage extraction process, including key phenolic species such as vanillic acid, caffeic acid, oleuropein, coumaric acid and gallic acid, identified by LC-MS/MS. This study highlights the potential for converting olive mill waste into valuable resources, promoting sustainable practices, and supporting a circular economy in the olive oil industry.
Keywords: Olive mill waste; Volatile fatty acids; Polyphenol recovery; Extraction